PELATIHAN PEMBUATAN APLIKASI ANDROID SEBAGAI BEKAL TECHNOPRENEURSHIP UNTUK PENINGKATAN DAYA EKONOMI MANDIRI ALUMNI SMK DI PEKANBARU - Nurliana Nasution; Mhd Arief Hasan; David Setiawan (LPPM Universitas Abdurrab, 2018)
The development of mobile-based technology is now very advanced and often used for the world of IT, Business, education and learning media. Along with the needs of the android-based programmers in Pekanbaru City is still far from the expected amount when the income earned by mastering this programming is very large proven the number of new rich people who succeed through this android mobile based programming mastery. This is the interest of teachers in SMK Pekanbaru City. If this is already the expertise gained by their alumni. that this training needs to be done, because the needs of SMK who want self-supporting their alumni by mastering the manufacture of mobile-based applications.